Analisis Majas Perbandingan Dalam Novel Sepasang Yang Melawan (2) Karya Jazuli Imam - Rianti Rianti; Septiana Pradyta (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this research is to describe the figurative language used in the novel “A Pair Against (2)” by Jazuli Imam and to find out the author's style of writing. The type of research used is descriptive qualitative, the target of this research is to describe the comparative figure of speech in the novel "A Pair Against (2)" by Jazuli Imam. The data source in this study is the entire text contained in the novel. Data collection techniques in this study were carried out by recording techniques and classifying the findings of comparative figurative sentences. In this research, the researcher uses the theory of comparative figure of speech by Henry G. Tarigan as the basis for the comparative figure of speech to be studied. Based on the results of the analysis, the novel "A Pair Against (2)" contains several comparative figures of speech, namely: 3 figures of speech for parable/simile, 4 figures of speech for metaphor, 1 figure of speech for depersonification, 2 figure of speech for personification, 1 figure of speech for anticipation/prolepsis, 4 figure of speech for correction/epanortosis, and 2 major periphrases. Thus, a literary work cannot be separated from the figure of speech because this figure of speech is the most important thing in a literary work. The author uses this figure of speech to create a beautiful writing. Through the figures of speech contained in literary works, literary works become more lively and varied, so as to avoid things that are monotonous